A COMPARATIVE STUDY OF RTV-225 SILICONE ELASTOMER AND NATURAL RUBBER BASED THERMO-ELASTOMER FOR SOFT ROBOTIC APPLICATIONS - Khan, M. B.; Smithmaitrie, P.; Kalkornsurapranee, E. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
Leveraging on material compliance, soft robots of today are mostly fabricated using silicone elastomers with reported long curing times. Hence, this opens possibilities to explore new materials for fabrication. In this paper, a recently patented natural rubber thermo-plastic elastomer (NRTE) is presented in comparison to RTV-225 silicone elastomer. NRTE inherits a mix of elasto-plastic behavior with ability to be easily formed by heating. Under normal operating conditions, it shows a unique self-healing-like behavior that allows multiple times of reuse. The post processing takes less than 2 minutes to cure. This reduces time to fabricate CiSS and CbSS soft structures. Mechanical properties of both elastomers are reported and compared by performing a tensile strength test. Additionally, this study presents design, fabrication, and testing of CiSS and CbSS simple soft structures which are made of NRTE and RTV-225 elastomers. The results reveal that NRTE has a potential to be used in prototyping of soft robotic structures.